Herpes simplex virus 1 and 2 in herpes genitalis: A polymerase chain reaction-based study from Kerala - Rani Mathew; Bangalath Najeem; Kunjumani Sobhanakumary; Beena Sunny; Carol Pinheiro; Balakrishnan Anukumar (Wolters Kluwer Medknow Publications, 2018)
Background: Herpes genitalis is an ulcerating sexually transmitted infection, the clinical importance of which lies in its ability to produce painful and recurrent disease in addition to its potential role as a cofactor in acquisition and transmission of human immunodeficiency virus. In recent years, there are increasing reports of genital herpes due to herpes simplex virus (HSV)-1 from various parts of the world. Molecular diagnostic methods such as polymerase chain reaction (PCR) have got both diagnostic and prognostic significance in genital herpes. Aims: The present study was designed to identify the viral serotype in herpes genitalis patients in our locality, using PCR. Materials and Methods: The specimens from forty herpes genitalis patients were subjected to nested PCR and results were evaluated. Results: PCR was positive for HSV in 83% of cases, of which 58% were due to HSV-1. HSV-2 accounted for maximum number of recurrent herpes. Limitation: Higher sample size would have been more representative. Conclusion: A rising trend of type 1 HSV was observed in herpes genitalis in south India probably due to increasing practice of orogenital sex.